The compare for structural, mechanical and thermal properties between poly (vinyl alcohol) and graphene /poly (vinyl alcohol) nanocomposites - Aziz, Salah M. Abd Ul; Hassoon, 2Zainab Karam (International Journal of Psychosocial Rehabilitation, 2020)
Graphene/polymer nanocomposites have created escalated attention because of their extraordinary properties. There are two main components for property improvements Interface interactions and scattering among the polymer matrix and graphene. In graphene/ poly (vinyl alcohol) (PVA) nanocomposites, as a rule, gets more huge property improvements than neat (PVA) as indicated by the previous literature. The improved properties of polymer nanocomposites as contrasted with neat polymers are just carried out in powerful interfacial adhesion and the existence of well-scattered nanoparticles. In this research, nanocomposite films were synthesised dependent on poly (vinyl alcohol) (PVA) filled with fine well-scattered graphene nanoparticles. The prepared films were distinguished by Fourier transform infrared spectrum (FT-IR) and X-ray diffraction (XRD) analysis. When incorporating graphene with the neat (PVA) the elongation and tensile strength at break arrive maximum qualities, indicating increments by 34% and 212, respectively.